Analisis Hubungan Antara Teknologi dan Politik: Studi Kasus Mengenai Pengaruh Teknik Komunikasi Digital Terhadap Partisipasi Politik - Muhammad Iqtar Rizky; Baiqturahman Ivansyah Putra; Raditia Rahman Triatmaja; Bryan Adi Nugraha; Wicky Alfiansyah Putra; Denny Oktavina Radianto (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This study aims to analyze the relationship between technology and politics, focusing on the influence of digital communication techniques on political participation. In the digital era, information and communication technology has changed the political landscape significantly. This study uses qualitative and quantitative approaches to gain a comprehensive understanding of the impact of technology on people's political participation. The methods used in this research are interviews with respondents who are involved in political activities and a survey of a representative population. The collected qualitative and quantitative data will be analyzed using content analysis techniques and descriptive statistics. This research also involves case studies to illustrate how digital communication technologies have affected political participation at individual and collective levels. The results of this study are expected to provide a better understanding of how digital communication technology influences people's political participation. In addition, this research is also expected to provide insights on changes in political and communication power structures as a result of the adoption of new technologies. In the ever-evolving digital era, information and communication technology has changed the way we interact, including in the political context. Developments in digital communication technology, such as the internet, social media, and instant messaging applications, have provided easier and faster access to political information and facilitated more active political participation. Therefore, it is important to understand the relationship between technology and politics and its impact on people's political participation. In this context, an analysis of the influence of digital communication techniques on political participation is relevant. Digital communication techniques, such as the use of social media to share political information, participate in online political discussions, and engage in political campaigns through digital platforms, can provide new opportunities for individuals and groups to participate in political activities. However, the effects of using communication technology digital impact on political participation is not always positive. Keywords: technology, politics, communication